2022
DOI: 10.1111/ajae.12343
|View full text |Cite
|
Sign up to set email alerts
|

Price risk and small farmer maize storage in Sub‐Saharan Africa: New insights into a long‐standing puzzle

Abstract: Maize prices fluctuate across seasons in rural markets in many low income countries, and agricultural households struggle to sell their grain at an optimal time. We provide new insight into a persistent puzzle: small farmers in lowincome countries tend to sell their maize at harvest, when prices are low, rather than storing and waiting until prices increase later in the year. Our descriptive analysis uses 20 years of data from 1038 retail markets in 30 African countries to demonstrate that the lean season pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…Similarly, groundnut prices did not increase in only 4 years, and soybean prices did not increase in 7 years. These findings are consistent with recent evidence from Cardell and Michelson (2022) who found that across 30 countries in SSA over 20 years maize prices did not rise between harvest and lean season nearly 16% of the time on average. In total, this information suggests that legume crops are relatively more viable as a stored commodity to exploit price arbitrage opportunities compared to maize in Malawi.…”
Section: Setting and Experimental Designsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, groundnut prices did not increase in only 4 years, and soybean prices did not increase in 7 years. These findings are consistent with recent evidence from Cardell and Michelson (2022) who found that across 30 countries in SSA over 20 years maize prices did not rise between harvest and lean season nearly 16% of the time on average. In total, this information suggests that legume crops are relatively more viable as a stored commodity to exploit price arbitrage opportunities compared to maize in Malawi.…”
Section: Setting and Experimental Designsupporting
confidence: 92%
“…In this study, we focus on legumes, specifically groundnuts and soybeans, because their prices typically exhibit relatively larger seasonal price variations and fetch higher prices compared to maize. This is in line with empirical evidence from some recent studies in SSA that find limited price seasonality in maize during certain seasons (Abass et al, 2014; Burke et al, 2019; Cardell & Michelson, 2022; Channa et al, 2022). The Ministry of Agriculture's monthly price data for Malawi from 1989 to 2017 also showed larger intraseasonal variations in average prices for legumes relative to maize between harvest and lean season (Appendix 1).…”
Section: Setting and Experimental Designsupporting
confidence: 90%
“…The other insight relates to interventions aimed at motivating storage in rural Africa. Indeed, one of the persisting puzzles has been the low storage uptake by farmers in sub‐Saharan Africa (e.g., Cardell & Michelson, 2022). Whether selling the crop at harvest or storing it for later sale reduces the risk of becoming a target of violence is an important question for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Findings suggest that storage conditions (Aggarwal et al. , 2018; Tesfaye and Gebremariam, 2020), liquidity constraints (Cardell and Michleson, 2023; Kadjo et al. , 2018; Stephens and Barrett, 2011), and subjective preferences like risk attitudes (Ruhinduka et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have focused on China and other developing countries, conducting research on farmers' price-risk-management behaviors in these countries. Findings suggest that storage conditions (Aggarwal et al, 2018;Tesfaye and Gebremariam, 2020), liquidity constraints (Cardell and Michleson, 2023;Kadjo et al, 2018;Stephens and Barrett, 2011), and subjective preferences like risk attitudes (Ruhinduka et al, 2020;Bellemare et al, 2021) can affect farmers' selling behaviors and their management of agricultural product price risk. Although these previous studies greatly contributed to our understanding of farmers' agricultural risk management, several gaps remain.…”
Section: Introductionmentioning
confidence: 99%